2018
DOI: 10.3390/cryst8040160
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Edge Dislocations with Graphene Nanosheets in Graphene/Fe Composites

Abstract: Abstract:Graphene is an ideal reinforcement material for metal-matrix composites owing to its exceptional mechanical properties. However, as a 2D layered material, graphene shows highly anisotropic behavior, which greatly affects the mechanical properties of graphene-based composites. In this study, the interaction between an edge dislocation (b = 1/2 (111)) and a pair of graphene nanosheets (GNSs) in GNS reinforced iron matrix composite (GNS/Fe) was investigated using molecular dynamic simulations under simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The extraordinary electronic properties, such as high electron mobility under room temperature [ 14 ], make graphene ideally suited for the fabrication next generation logic device [ 15 ]. Graphene’s ultra-high intrinsic strength [ 16 ] make it a good candidate as reinforcement [ 17 ]. For instance, a graphene/poly nano-composite material is reported to give a 76% increase in tensile strength and a 60% increase in Young’s modulus [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary electronic properties, such as high electron mobility under room temperature [ 14 ], make graphene ideally suited for the fabrication next generation logic device [ 15 ]. Graphene’s ultra-high intrinsic strength [ 16 ] make it a good candidate as reinforcement [ 17 ]. For instance, a graphene/poly nano-composite material is reported to give a 76% increase in tensile strength and a 60% increase in Young’s modulus [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the rst graphene reinforced Al matrix composite was reported in 2011, graphene reinforced Al, Cu, Ni, Mg, Fe alloy, [9][10][11][12][13] and intermetallic compound matrix composites have been obtained by different processing techniques, including powder metallurgy, 14 melting and solidication, 15 thermal spray, 16 electrochemical deposition, 17 etc. Although great success has been achieved, it was difficult to synthesize high quality graphene reinforced composites in the previous studies because the dispersion and uniformity of graphene could not be well controlled, where procedures such as metallurgy, melting, spray and deposition were involved.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is believed to be strongly chemisorbed on iron due to a rich interaction between Fe and C, which is beneficial for interfacial strength [22,29] and also affects load transfer on graphene-reinforced metal matrix composites. In our previous work [30], we studied the mechanical properties of graphene nanosheet (GN)-reinforced iron matrix composite by MD simulation and the results showed that when the GN was parallel to the {110} plane of iron matrix, the shear modulus and yield stress of the composite increased by 107% and 1400%, respectively, compared to unreinforced Fe. However, a systematic study about adhesion energy of graphene on iron substrate is still lacking.…”
Section: Introductionmentioning
confidence: 99%